DARA ANTA (SEBUAH TRAGEDI DARI LEGENDA MASYARAKAT KETUNGAU HILIR KABUPATEN SINTANG - Wanda, Apriyanti; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract?Dara Anta choreograph inspired by the legend of Ketungau Hilir?s people of Sintang District. Legend is a story that is considered true, the story is related to historical figures, it has been spiced with magic, wonders, and special features. The legend of Dara Anta is a tragedy that happened in the past, still a story until now among the peoples of Ketungau Hilir, when a woman named Dara Anta became a stone due to anger because of her husband?s betrayal. This phenomenom turns out to be the basic idea in creating "Dara Anta" choreograph which in a dance-theater form or a dance with story. Dara Anta choreograph applies and goes through some methods in its making-process such as exploration, processing, application, evaluation, and revision. This performance brings out an interesting aesthetic from the dance and music, and it becomes not just a dance show, but its music is as well attractive. Apart from that, the choreograph combines uniqueness of Dayak traditional dance movements and Dayak creations. This is not just an entertaining performance, but it consists innovation in developing traditional dance, educational aspect and as well morality message.? Keyword: Dance Analyzing, Dara Anta, Legend, Method and Creational Process